IMPLEMENTASI PROGRAM KELUARGA HARAPAN DALAM MENINGKATKAN KESEJAHTERAAN DITINJAU DARI NILAI DASAR EKONOMI ISLAM (STUDI PADA PKH DI DESA KAMBUNO KECAMATAN BULUKUMPA KABUPATEN BULUKUMBA) - hamdi, Hasniar; Fathurrahman, Fathurrahman; Sirajuddin, Sirajuddin (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Bulukumba Regency is one of the districts that has welfare problems (poverty), one of which is in the village of Kambuno. this village is one of the villages that received social assistance in the form of the Family Hope Program (PKH). The purpose of this study is to find out, understand and explain how the implementation of the Family Hope Program (PKH) improves people's welfare when viewed from the basic values of Islamic economics in Kambuno Village. The type of research used is "Case Study". Case study is research that focuses on a particular case with the aim that it can be analyzed and observed. The data sources in this study were primary data in the form of direct interviews with relevant informants and secondary data in the form of lists of PKH beneficiaries. The results of this study indicate that the implementation of PKH when viewed from the basic values of Islamic economics, namely in terms of tafakul does not provide social security to PKH participants from a fairness perspective, it has not been fully implemented, this is indicated by the inaccuracy of the target of receiving PKH assistance, as well as delays in disbursement. funds that are sometimes experienced by some KPM, and seen from the value of responsibility that has gone well, this is shown by the assistants or PKH participants having fulfilled their rights and obligations keywords: PKH, justice, responsibility, tafakul (social security),